2022
DOI: 10.3390/jcm11071764
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Therapy Improves Tinnitus-Related Distress in Mildly Distressed Patients with Chronic Tinnitus and Mild-to-Moderate Hearing Loss: A Randomized-Controlled Cross-Over Design

Abstract: Background: The psychological effects of hearing aids and auditory training are underinvestigated. Objective: To assess the short- and long-term effects of an industry-developed auditory training on tinnitus-related distress, perceived stress, and psychological epiphenomena in patients with chronic tinnitus and mild-to-moderate hearing loss. Method: One-hundred-seventy-seven gender-stratified patients were randomized to an immediate [IIG] or delayed [DIG] intervention group. Following binaural hearing aid fitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 72 publications
0
8
0
2
Order By: Relevance
“…For individuals with hearing loss, hearing aids are the initial treatment option of choice, where applicable. Preliminary evidence suggests that the use of hearing aids can benefit tinnitus-related distress for patients with mild-to-moderate hearing loss 106 . In cases of profound hearing loss, a cochlear implant should be considered 117 118 119 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For individuals with hearing loss, hearing aids are the initial treatment option of choice, where applicable. Preliminary evidence suggests that the use of hearing aids can benefit tinnitus-related distress for patients with mild-to-moderate hearing loss 106 . In cases of profound hearing loss, a cochlear implant should be considered 117 118 119 .…”
Section: Discussionmentioning
confidence: 99%
“…Hearing aids may positively influence tinnitus-related distress 104 105 . For example, a recent randomized cross-over study demonstrated that a specific hearing aid fitting could reduce tinnitus-related distress in individuals with chronic tinnitus and mild-to-moderate hearing loss 106 . Whether hearing aids can also have a positive effect on cognitive difficulties is controversially discussed 80 107 108 109 110 .…”
Section: Treatment Optionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean improvement in the THI total score corresponds to the minimal clinically relevant change for evaluating treatment effects [ 53 ]. Since it was shown that THI significantly predicts depression, anxiety, and stress [ 54 ], we can conclude that a reduction in functional limitations is accompanied by the amelioration of distress, even though beneficial psychological knock-on effects deserve further investigation [ 55 ].…”
Section: Discussionmentioning
confidence: 99%